A Religião no espaço público da sociedade plural: considerações iniciais sob a ótica da fé em Jesus Cristo = Religion in the Public Space of Plural Society : Initial Considerations from the Perspective of Faith in Jesus Christ - Steffen, Carlos José Monteiro (Teocomunicação, 2018)
Does the discourse of faith take place in the public space of modern, pluralistic and democratic society? The article seeks to reflect on this issue, placing it in the context of the reciprocal relations Church and modernity. It presents the Christian faith as offering of meaning to man and modernity as a complex reality, which should not simply be identified with the process of secularization. The contributions of Joseph Ratzinger, Charles Taylor, John Rawls and Jürgen Habermas to the debate on this issue are highlighted.